2021
DOI: 10.1038/s41598-021-83684-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic loci affecting body mass index through interaction with multiple environmental factors using structured linear mixed model

Abstract: Multiple environmental factors could interact with a single genetic factor to affect disease phenotypes. We used Struct-LMM to identify genetic variants that interacted with environmental factors related to body mass index (BMI) using data from the Korea Association Resource. The following factors were investigated: alcohol consumption, education, physical activity metabolic equivalent of task (PAMET), income, total calorie intake, protein intake, carbohydrate intake, and smoking status. Initial analysis ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“… Polimanti et al (2021) reported a strong association of lifetime polysubstance dependence with lifetime suicidality and using StructLMM, identified multivariate G×E interaction loci ( LCAT , p = 1.82 × 10 –7 ; TSNAXIP1 , p = 2.13 × 10 –7 ; CENPT, p = 2.32 × 10 –7 ; PARD6A , p = 5.57 × 10 –7 ) of suicidality that interact with 4 substance dependences such as opioid, cocaine, nicotine, and polysubstance dependences (15,557 American participants in the Yale-Penn cohort) ( Polimanti et al, 2021 ). We previously applied this StructLMM to BMI in 8,155 Korean samples from the Korea Association Resource to evaluate interactions with seven factors including alcohol consumption, education, income, total calorie intake, protein intake, carbohydrate intake, and smoking status ( Jung et al, 2021 ). This previous study using StructLMM identified genome-wide significant interaction loci (rs2391331 in the EFNB2 ; p = 5.03 × 10 –10 ) with BMI, and BF analyses showed that six environmental factors, except for carbohydrate intake, contributed to the interaction with this SNP on BMI ( Jung et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Polimanti et al (2021) reported a strong association of lifetime polysubstance dependence with lifetime suicidality and using StructLMM, identified multivariate G×E interaction loci ( LCAT , p = 1.82 × 10 –7 ; TSNAXIP1 , p = 2.13 × 10 –7 ; CENPT, p = 2.32 × 10 –7 ; PARD6A , p = 5.57 × 10 –7 ) of suicidality that interact with 4 substance dependences such as opioid, cocaine, nicotine, and polysubstance dependences (15,557 American participants in the Yale-Penn cohort) ( Polimanti et al, 2021 ). We previously applied this StructLMM to BMI in 8,155 Korean samples from the Korea Association Resource to evaluate interactions with seven factors including alcohol consumption, education, income, total calorie intake, protein intake, carbohydrate intake, and smoking status ( Jung et al, 2021 ). This previous study using StructLMM identified genome-wide significant interaction loci (rs2391331 in the EFNB2 ; p = 5.03 × 10 –10 ) with BMI, and BF analyses showed that six environmental factors, except for carbohydrate intake, contributed to the interaction with this SNP on BMI ( Jung et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously applied this StructLMM to BMI in 8,155 Korean samples from the Korea Association Resource to evaluate interactions with seven factors including alcohol consumption, education, income, total calorie intake, protein intake, carbohydrate intake, and smoking status ( Jung et al, 2021 ). This previous study using StructLMM identified genome-wide significant interaction loci (rs2391331 in the EFNB2 ; p = 5.03 × 10 –10 ) with BMI, and BF analyses showed that six environmental factors, except for carbohydrate intake, contributed to the interaction with this SNP on BMI ( Jung et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%